Comparing municipal entrepreneurship support: Insights from Polish and Latvian municipalities - Skica, Tomasz; Rodzinka, Jacek; Ociepa-Kicińska, Elżbieta; Czyżycki, Rafał; Sauka, Arnis (Rozwój Regionalny i Polityka Regionalna, 2024)
Municipalities play a particularly important role including the creation of appropriate living conditions and organising the proper functioning and development of the economy. This study examines how Polish and Latvian local governments foster entrepreneurship and the efficacy of financial and non-financial tools employed by local authorities in facilitating entrepreneurial endeavors. Analyzing data from 896 Polish municipalities and 119 Latvian units, the study identifies differences in support mechanisms and their impact on entrepreneurship dynamics. The results reveal differences in support mechanisms between the two countries and their correlation with the establishment of new enterprises. The findings offer insights for policymakers to tailor strategies conducive to local entrepreneurship.